A Dual‐domain Engineered Antibody for Efficient HBV Suppression and Immune Responses Restoration - Yichao Jiang; Xiaoqing Chen; Xinya Ye; Can Wen; Tao Xu; Chao Yu; Wenjing Ning; Guosong Wang; Xinchu Xiang; Xiaomin Liu; Yalin Wang; Yuanzhi Chen; et al. (Advanced Science, 2024)
Abstract Chronic hepatitis B (CHB) remains a major public health concern because of the inefficiency of currently approved therapies in clearing the hepatitis B surface antigen (HBsAg). Antibody‐based regimens have demonstrated potency regarding virus neutralization and HBsAg clearance. However, high dosages or frequent dosing are required for virologic control. In this study, a dual‐domain‐engineered anti‐hepatitis B virus (HBV) therapeutic antibody 73‐DY is developed that exhibits significantly improved efficacy regarding both serum and intrahepatic viral clearance. In HBV‐tolerant mice, administration of a single dose of 73‐DY at 2 mg kg−1 is sufficient to reduce serum HBsAg by over 3 log10 IU mL−1 and suppress HBsAg to < 100 IU mL−1 for two weeks, demonstrating a dose‐lowering advantage of at least tenfold. Furthermore, 10 mg kg−1 of 73‐DY sustainably suppressed serum viral levels to undetectable levels for ≈ 2 weeks. Molecular analyses indicate that the improved efficacy exhibited by 73‐DY is attributable to the synergy between fragment antigen binding (Fab) and fragment crystallizable (Fc) engineering, which conferred sustained viral suppression and robust viral eradication, respectively. Long‐term immunotherapy with reverse chimeric 73‐DY facilitated the restoration of anti‐HBV immune responses. This study provides a foundation for the development of next‐generation antibody‐based CHB therapies.